Prognostic relevance of motor tests in elite girls' soccer: a five-year prospective cohort study within the German talent promotion program - Höner, O.; Raabe, J.; Murra, D.; Leyhr, D. (Science and Medicine in Football, 2019)
Introduction: While research has provided valuable information about talent predictors, there is a gap regarding female soccer. This study analyzed the prognostic relevance of motor tests for players' future selection level in female soccer and assessed the role of sex as a moderator variable.